Complexidade econômica e padrão de exportações no Brasil: uma análise para o período 1995-2016 - Larruscaim, Igor de Menezes (2020)
The theory of economic complexity comes up as a new approach to explain the economic development of countries. In this conception, the goods produced by an economy represent the knowledge accumulated in this productive structure, also represents the productive capacities. The economies that have a wide and diverse set of these productive capacities have, for the most part, higher levels of development. Authors such as Ricardo Hausmann and Cesar Hidalgo made a great contribution to the construction of this new approach. Based on concepts from physics, the authors developed a methodology for measuring the level of sophistication of economies. Through the concepts of Product Space, which uses network analysis to identify the types of connections between goods exported by countries and especially the Index of Economic Complexity, which considers the countries' exports to represent the productive structure of these economies and indicates a higher level of complexity for the more diversified and specialized structures in goods that few countries produce. This study aims to identify whether the behavior of the economic complexity index for Brazil can represent the existence of changes in the Brazilian productive structure over the period 1995-2016. The Brazilian case is emblematic; the country has been going through several and impactful changes in its economy since the 1990s, such as the stabilization of the inflationary process, trade opening, changes in the exchange rate system, in addition to changes in the external scenario such as the increase external demand for commodities and the international financial crisis. Even after the stabilization and the return of economic growth during the 1990s and 2000s, the country was not able to maintain itself on a sustained growth trajectory, returning to resection in the mid-2010s. All these events caused changes in the pattern of exports in Brazil and the intention is to verify whether the index captured these changes and whether they represent a change in the sophistication of our production structure or if they only reflect changes in the international trade flow. Although, the study aims to describe the main concepts of the complexity approach and what their contributions to economic theory and limitations are; to identify the existence of a pattern of specialization in Brazilian exports throughout this period and to analyze the national scenario from the 1990s on concerning the economic changes that occurred in the country. For this purpose, were used data on Brazilian exports from that period, the analysis can identify that events such as the opening of trade did not have an immediate effect on Brazilian exports and that from the so-called commodity boom and the change in terms of trade, the country passes to increase your pattern of specialization. The complexity index captured, to some degree, the changes in the Brazilian export basket, but it showed limitations in making an accurate representation of these changes, as it presents a great sensitivity with variations in export prices causing marked changes in the index that do not correspond in fact to changes in productive structure.